Big Data in Marketing: Opportunities and Threats - Woźniczka , Jarosław (Studia Oeconomica Posnaniensia, 2018)
Thanks to the development of information and telecommunications technologies, data digitalization and the growing tendency to use the Internet and various devices connected to the Internet, the rapid increase of the amount of data collected in IT systems can be observed. Big data is currently considered to be one of the key resources of enterprises having access to them and a breakthrough in management and marketing, especially in marketing research and data analysis. At the same time, the use of large data sets raises various management and methodological challenges and ethical dilemmas. The aim of the paper is to present selected opportunities and threats related to the use of big data in marketing. It contains the current world literature review and a synthesis of the selected topics.